A’ meş Süleyman Bin Mihran ve hadis ilmindeki yeri - Gültekin, Hüseyin (My University, 2002)
A'meş, Süleyman bin Mihrân ve Hadis İlmindeki Yeri isimli bu tez bir giriş ve iki ana bölümden oluşmaktadır. Hicrî Birinci ve İkinci Asırlarda Kûfe ve Hadis İlmi adını alan giriş bölümünde A'meş'in, hayatını geçirdiği Kûfe'nin coğrafi, ictimai ve siyasi durumuyla, hicrî birinci ve ikinci asırlarda hadis ilmindeki gelişmelere yer verilmiştir. A'meş'in Hayatı ve İlmî Şahsiyeti isimli birinci bölümün ilk kısmında A'meş'in doğumuna, ölümüne ve bazı insani özelliklerine yer verilmiş; ikinci kısmında ise tahsil ettiği ilimler ile hoca ve talebeleri incelenmiştir. Tezin ikinci bölümü A'meş'in Hadisçiliği adını almıştır. Bu bölümde A'meş hakkında yapılan tenkit ve övgülere, ayrıca, A'meş'in hadis sahasındaki değişik görüşlerine yer verilmiştir. Sonuç bölümünde ise araştırmaların sonucunda varılan neticelere kısaca değinilmiştir.

This study called Life of A'meş, Süleyman b. Mihrân and His Importance at Hadiths consists of one introduction and two main parts. In the introduction part, information about the places where Süleyman b. Mihrân lived, such Kûfe and about the political situation and study of Hadith of his time has been given. The first part Süleyman b. Mihrân's life, his scientific personality consists of two titles. In the first part information about Süleyman b. Mihrân's birth, childhood, family, education life, moral and ethic personality and his death have been given. In the second part under the title His scientific personality information about his scientific travels, knowledge of fiqh and history have been examined. His masters and students have been examined in detail in this part, too. The second part called Süleyman b. Mihrân's study of Hadiths consists of two titles. His position in study of Hadiths has been tried to establish by taking into consideration his scientific travels and the critical reviews which were made about him under the two titles.
Keywords: Hadis; Islam Dini Hadisler